Tipping Points – Key to a Deep Understanding of Complex Dynamic Systems by Learners? - Fögele, Janis; Mehren, Rainer; Rempfler, Armin (Journal of Geography Education, 2020)
The empirically confirmed GeoSysKo-model for geographical system competence is primarily oriented towards quantitative system properties. Qualitative characteristics, which are more important for the profound understanding of complex dynamic systemsfrom a systems theory perspective, are not sufficiently considered. The more recent studies on tipping points represent a fundamental expansion of knowledge in thefunctional and process understanding of natural,social and human-environmental systems.Their analysis in this paper forms the basis for deriving theoretically and empirically founded system properties, the operationalization of which should enable or improve the acquisition of a qualitative understanding of systems by learners. A corresponding extension of the GeoSysKo-model could provide a strong impulse in empirical teaching/learning research on systems thinking in Geography Education and beyond.
Keywords: systems thinking, competence modelling, tipping points, system-specific properties